(untitled) (Journal of Hama University, 2026)
This study was tested on (21) rabbits. This study aimed to identify the protective effect of black seed oil against quails, with the exception of rabbits treated with gentamicin. (3) groups were used, where each group included (7) rabbits and they were divided asfollow : The first group was the natural control group, which was given only water and food, while the second group was given gentamicin at a concentration of (80) mg/kg of body weight intraperitoneally for seven consecutive days, while the third group was given gentamicin at a concentration of (80) mg/kg of body weight intraperitoneally and was simultaneously given black seed oil orally at a rate of (1) ml/kg of body weight for seven consecutive days. The results in the second group showed a significant increase in the levels of the following parameters: urea, creatinine, and uric acid, compared with the normal control group, while the results in the third group showed a significant decrease in the levels of the following parameters: urea, creatinine, and uric acid, compared with the second group.